MODERNIZING THE DESCRIPTIVE GEOMETRY CURRICULUM THROUGH INNOVATIVE PEDAGOGICAL APPROACHES - Yusubjonov Jonibek Farkhod ugli (Bright Mind Publishing, 2025)
Innovative pedagogical approaches aim to enhance student engagement, understanding, and application of complex concepts in higher education. In the context of Descriptive Geometry, modernizing the curriculum through active learning, project-based learning, digital tools, and collaborative strategies can foster spatial reasoning, visualization skills, and applied problem-solving. This study explores methodologies for integrating innovative pedagogical practices into Descriptive Geometry courses, assessing their effectiveness in improving learning outcomes. Using the IMRaD framework, the research combines literature review, curriculum analysis, and experimental implementation in classroom and laboratory settings. Results indicate that innovative approaches increase student motivation, engagement, and comprehension, while promoting collaborative and self-directed learning. The discussion evaluates challenges, implementation strategies, and future directions, and the conclusion emphasizes the importance of pedagogical innovation in modernizing Descriptive Geometry education.
Keywords: Descriptive Geometry, Innovative Pedagogy, Curriculum Modernization, Active Learning, Project-Based Learning, Digital Tools, STEM Education, Higher Education.